Condenados pelo Tribunal do Júri da Comarca de Palmas/Tocantins: um estudo sobre a relação entre a condição dos apenados, a exclusão social e a privação de direitos e garantias fundamentais - Almeida, Lavínia de Jesus Dória de (Universidade Federal do Tocantins, 2020)
This article discusses the importance of the effective application of the constitutionally provided fundamental rights and guarantees, since their satisfaction is configured in the observance of the dignity of the human person, inherent to all without distinction, as addressed by important authors, among which stands out. the philosopher Immanuel Kant, thus being a significant instrument for reducing social inequalities and the propensity for crime. The work is substantiated by a survey of the socioeconomic reality of those convicted by the Court of Appeals of the County of Palmas/TO, by consulting the records made available by the 1ª Criminal Court of Palmas, the cases judged in the first half of 2019, allowing to know relative aspects age, education, profession and place of residence.